Metabolic reprogramming and therapeutic targeting in non-small cell lung cancer: emerging insights beyond the Warburg effect - Cai, Hong; Zhang, Feng; Xu, Fang; Yang, Chunhui (Frontiers in Oncology, 2025)
Non-small cell lung cancer (NSCLC) remains a leading cause of cancer-related mortality worldwide. Recent advancements have illuminated the intricate metabolic reprogramming that underpins NSCLC progression and resistance to therapy. Beyond the classical Warburg effect, emerging evidence highlights the pivotal roles of altered lipid metabolism, amino acid utilization, and the metabolic crosstalk within the tumor microenvironment (TME). This review delves into the latest discoveries in NSCLC metabolism, emphasizing novel pathways and mechanisms that contribute to tumor growth and survival. We critically assess the interplay between cancer cell metabolism and the TME, explore the impact of metabolic heterogeneity, and discuss how metabolic adaptations confer therapeutic resistance. By integrating insights from cutting-edge technologies such as single-cell metabolomics and spatial metabolomics, we identify potential metabolic vulnerabilities in NSCLC. Finally, we propose innovative therapeutic strategies that target these metabolic dependencies, including combination approaches that enhance the efficacy of existing treatments and pave the way for personalized metabolic therapies.